A Multidisciplinary Methodology for Technological Knowledge, Characterization and Diagnostics: Sandstone Facades in Florentine Architectural Heritage - Irene Centauro; Jacopo Giuseppe Vitale; Sara Calandra; Teresa Salvatici; Claudio Natali; Michele Coppola; Emanuele Intrieri; Carlo Alberto Garzonio (Applied Sciences, 2022)
The Historic Center of Florence, a UNESCO World Heritage Site, includes many examples of architecture characterized by rough-hewn rusticated block facades—a very common masonry technique in the Florentine Renaissance—made in Pietraforte sandstone. The latter features numerous criticalities related to its intrinsic characteristics and to decay phenomena that are due to weathering and pollution. A multidisciplinary methodology has been developed starting from historic analysis and architectural survey to a complete optometric, mechanical, physical, mineralogical, and petrographic characterization of rough-hewn rusticated blocks, applied to the case study of the Palazzo Medici Riccardi facades. The studies performed in this work cover several research fields, from architecture to geology, going through material diagnostics, and aim at improving knowledge and designing new restoration solutions for Pietraforte building-material criticalities. The research proposes an operative protocol aimed at supporting restoration projects and monitoring plans, with the aim to protect historical, architectural, and artistic cultural heritage and to safeguard the people who visit the city of Florence every year.